Real-world efficacy and safety of eribulin in advanced and pretreated HER2-negative breast cancer in a Spanish comprehensive cancer center - Milana Bergamino Sirvén; Adela Fernández-Ortega; Agostina Stradella; Idoia Morilla; Catalina Falo; Silvia Vázquez; Roser Castany; Rafael Villanueva; Sabela Recalde; Valentí Navarro Pérez; Miguel Gil-Gil; Sonia Pernas (BMC, 2019)
Abstract Background Eribulin improves survival in pre-treated HER2-negative advanced breast cancer (ABC). However, limited data exist on co-morbidities and central nervous system (CNS) efficacy. The purpose of this study was to review eribulin's efficacy and safety in everyday clinical practice with special focus on age, body mass index (BMI) and central nervous system (CNS) activity. Methods An observational study was conducted in a series of HER2-negative ABC patients treated from January'14-December'17 outside a clinical trial. Objective Response Rate (ORR), Progression Free Survival (PFS), Overall Survival (OS), and association of clinical and pathological variables with outcome were evaluated. Results Ninety-five women were treated with at least one cycle of eribulin. Median age was 57 (33-83), and 18% were obese. Median number of prior chemotherapies for ABC was 3 (2-5) and 76% of patients had visceral metastases, including 21% with CNS involvement. Most tumors were estrogen receptor-positive (79%). ORR and stable disease (SD) at 6 months were 26.2 and 37.5%, respectively. Remarkably, relevant CNS efficacy was observed with eribulin: 20% of patients obtained partial response and 25% SD. Treatment was generally well tolerated and manageable, with 29% grade 3 and 10.9% grade 4 toxicities. Median PFS and OS were 4.1 months (CI95% 3.2-4.9) and 11.1 months (CI95% 9.5-14.7), respectively. Triple-negative disease, > 2organs involved and being younger than 70 years old were independent prognosis factors for worse OS in multivariate analysis. Most patients (75%) progressed in pre-existing metastases sites. Conclusion In everyday clinical practice, eribulin's efficacy seems similar to pivotal trials. CNS-efficacy was observed. TNBC, > 2 organs involved and being younger than 70 years old were independent prognosis factors for worse OS. Remarkably, less incidence of grade 4-toxicity compared to previous studies was found.